Análise e validação de uma escala de Otimismo para a realidade brasileira - Anna Cecília Chaves Gomes; Anderson Luiz Rezende Mól; Mayara Carla Marques (Revista Principia, 2019)
The present study proposed to present contributions regarding the bias of Optimism, with the objective of analyzing and validating a scale for Optimism in the Brazilian population. For this purpose, we used the TOV-R scale, it is also used in other countries. Although it was already translated in Brazil, it did not have its Construct Validity tested at the time. In relation to the sample, it consisted of 2,843 individuals. The statistical treatment of the data was done by means of Exploratory Factorial Analyzes (AFE), in which Cronbach’s alpha (α) was tested, with a result of 0.654 for the Optimism factor and 0.609 a for Pessimism, indicating reliability. Afterwards, a Confirmatory Factorial Analysis (AFC) was carried out, in which the negative correlation between the factors Optimism and Pessimism was perceived, something already expected due to the antagonism between the factors. However, it was not possible to validate Constructo because there is no Convergent and Discriminant Validation for the Optimism and Pessimism factors.